Preferensi Informasi dan Perilaku Bermedia Warganet di Akun Instagram Media Informasi Selebritas - Prof. YA Nunung Prajarto, Ph.D; Syaifa Tania, S.IP., M.A.; Mashita Phitaloka Fandia Purwaningtyas, S.IP., M.A. (FISIP Universitas Atma Jaya Yogyakarta, 2019)
The use of social media as a source of information is undeniably important. As it can be used to disseminate specific information, numbers of informational based accounts emerge in various topics, including Instagram accounts which specifically bring out celebrity news as their main information. Using a social informatics perspective approach, this paper aims to capture netizen behavior related to their media habit in accessing it. The results show these accounts emerge as the primary source of information about infotainment issues. However, netizens are unwilling to leave any digital trace related to their activities during accessing these accounts.